TESTAMENT MANCYPACYJNY ANTONIUSA SILVANUSA - Skalec, Aneta (Zeszyty Prawnicze, 2017)
Testament by Bronze and Balance of Antonius Silvanus Summary Roman wills, drafted per aes et libram, are mainly known from copies written in Greek on papyri. A will dating back to the 27th March 142 A.D., drafted by Antonius Silvanus, has survived the ravishes of time and thus allows us to understand the idea behind such forms of wills. Indeed, legal texts written by the Roman jurists and dating back to those times do not go into the contents of such wills. Hence, Silvanus’ will is a very important document which gives us an insight into the clauses which were regularly drafted into wills in that epoch. Silvanus’ final will and testament was written on a tabulae ceratae (a wooden tablet covered with a layer of wax). It was then meticulously closed in order to protect it from forgeries.